Design and implementation of a cascaded transformer coupled multilevel inverter‐based shunt active filter under different grid voltage conditions. (26th September 2018) - Dash, Ashish Ranjan; Panda, Anup Kumar; Patel, Ranjeeta; Penthia, Trilochan
Summary: The paper describes the design aspect and control logic of a cascaded multilevel inverter‐based shunt active filter by employing single‐phase toroidal core transformers in cascaded manner which enable to operate with a single DC‐link capacitor. The presented topology uses a single DC‐link capacitor, thus minimizing the number of sensors and controller for voltage balancing. The induction of cascaded toroidal core transformer makes the system highly reliable as it minimizes the failure possibility of the DC‐link capacitor. For reference current generation, a perfect harmonic cancelation (PHC) control technique is implemented which is insensitive to distorted input condition and frequency deviation. To verify the effectiveness of the PHC controller, it is compared with a well‐known i d ‐i q control technique under ideal and non‐ideal supply main conditions. Furthermore, the developed topology is validated through MATLAB simulation and its prototype along with a well‐known DSP‐based FPGA controller.